Translational balancing questioned: Unaltered glycosylation during disulfiram treatment in mannosyl‐oligosaccharide alpha‐1, 2‐mannnosidase‐congenital disorders of glycosylation (MAN1B1‐CDG). Issue 1 (20th March 2021) - Kemme, Lisa; Grüneberg, Marianne; Reunert, Janine; Rust, Stephan; Park, Julien; Westermann, Cordula; Wada, Yoshinao; Schwartz, Oliver; Marquardt, Thorsten
Abstract: MAN1B1‐CDG is a multisystem disorder caused by mutations in MAN1B1, encoding the endoplasmic reticulum mannosyl‐oligosaccharide alpha‐1, 2‐mannnosidase. A defect leads to dysfunction within the degradation of misfolded glycoproteins. We present two additional patients with MAN1B1‐CDG and a resulting defect in endoplasmic reticulum‐associated protein degradation. One patient (P2) is carrying the previously undescribed p.E663K mutation. A therapeutic trial in patient 1 (P1) using disulfiram with the rationale to generate an attenuation of translation and thus a balanced, restored ER glycoprotein synthesis failed. No improvement of the transferrin glycosylation profile was seen.